2011
DOI: 10.1002/hep.24041
|View full text |Cite
|
Sign up to set email alerts
|

Activation of alpha1-adrenergic receptors stimulate the growth of small mouse cholangiocytes Via calcium-dependent activation of nuclear factor of activated T cells 2 and specificity protein 1

Abstract: Small cholangiocytes proliferate via activation of Ca2+-dependent signaling in response to pathological conditions that trigger the damage of large cAMP-dependent cholangiocytes. Although our previous studies suggest that small cholangiocyte proliferation is regulated by the activation of Ca2+-dependent signaling, the intracellular mechanisms regulating small cholangiocyte proliferation are undefined. Therefore, we sought to address the role and mechanisms of action by which phenylephrine, an α1-adrenergic ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…18,19 Briefly, cDNA was generated by reverse transcription using 1 g of total RNA isolated using the RNA isolation kit (Bio-Rad, Hercules, CA) and the SuperScript III Reverse Transcription Kit (Invitrogen). Quantitative real-time PCR was performed on a MX 3005P PCR Instrument (Stratagene, San Diego, CA) as described.…”
Section: Mmp Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Briefly, cDNA was generated by reverse transcription using 1 g of total RNA isolated using the RNA isolation kit (Bio-Rad, Hercules, CA) and the SuperScript III Reverse Transcription Kit (Invitrogen). Quantitative real-time PCR was performed on a MX 3005P PCR Instrument (Stratagene, San Diego, CA) as described.…”
Section: Mmp Gene Expressionmentioning
confidence: 99%
“…Quantitative real-time PCR was performed on a MX 3005P PCR Instrument (Stratagene, San Diego, CA) as described. 18,19 Each sample was tested in triplicate. The PCR products were verified by melting curve analysis and by 1.8% agarose gel electrophoresis of the PCR product.…”
Section: Mmp Gene Expressionmentioning
confidence: 99%
“…Mz-Cha-1 cells, a human cholangiocarcinoma cell line, express four of seven P2X receptors (P2X 2 , P2X 3 , P2X 4 and P2X 5 ) (261). Normal rat cholangiocytes express P2X 2 , P2X 3 , P2X 4 and P2X 7 (70,71), with the P2X 4 receptor presumably being the dominant one (70).…”
Section: Calcium Signalingmentioning
confidence: 99%
“…Previous studies have shown that stimulation of a 1 -AR by the a 1 -AR agonist phenylephrine results in increased calcium transients, an effect that can be blocked by the use of the a 1 -AR antagonist prazosin (Thorlin et al 1998). In addition, glial a 1 -AR activation by NA promotes intracellular calcium release with downstream effects on membrane depolarisation, neurotransmitter release and cell proliferation (Legendre et al 1988;Stone et al 1999;Alpini et al 2011). It has also been demonstrated that a 1 -AR stimulation enhances glutamate uptake into cultured astrocytes (Hansson and Ronnback 1989;Fahrig 1993;Hertz et al 2010), and Ohashi et al (2007) showed that stimulation of a 1 -AR by phenylephrine suppressed stress-induced death and promoted cell survival in embryonic neural progenitor cells.…”
Section: Introductionmentioning
confidence: 97%